Great Connoiseurs examining a celebrated Cabinet Picture. - Jones, Thomas Howell (active 1824-1848) ? (Fores, S. W., 1830)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Great Britain -- Politics and government -- 1800-1837